2003
DOI: 10.1080/713840406
|View full text |Cite
|
Sign up to set email alerts
|

Improved Solubility and In Vitro Dissolution of Ibuprofen from Poloxamer Gel Using Eutectic Mixture with Menthol

Abstract: To improve the solubility and in vitro dissolution of poorly water-soluble ibuprofen with poloxamer and menthol, the effects of menthol and poloxamer 188 on the aqueous solubility of ibuprofen were investigated. The dissolution study of ibuprofen delivered by poloxamer gels composed of poloxamer 188 and menthol were performed. In the absence of poloxamer, the solubility of ibuprofen increased until the ratio of menthol to ibuprofen increased from 0:10 to 4:6, followed by an abrupt decrease in solubility above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…It was proven to be highly effective when applied to mucosal surfaces but a clear mechanistic understanding of permeation was not described (Carrasco et al, 1993). More recently similar effects have been shown when ibuprofen was combined with terpenes (Stott et al, 1998), menthol (Yong et al, 2003) and methyl nicotinate (Woolfson et al, 2000) to form a eutectic. This resulted in an increase in its permeation through the skin.…”
Section: Introductionmentioning
confidence: 81%
“…It was proven to be highly effective when applied to mucosal surfaces but a clear mechanistic understanding of permeation was not described (Carrasco et al, 1993). More recently similar effects have been shown when ibuprofen was combined with terpenes (Stott et al, 1998), menthol (Yong et al, 2003) and methyl nicotinate (Woolfson et al, 2000) to form a eutectic. This resulted in an increase in its permeation through the skin.…”
Section: Introductionmentioning
confidence: 81%
“…Terpenes are a class of natural compounds widely used in the pharmaceutical field and their interactions with drugs have been extensively evaluated since well before the advent of DES. Mixtures of borneol/menthol [20][21][22], and camphor/menthol [23,24], were proposed as vehicles for transdermal delivery [5] while mixtures of thymol with ibuprofen [25] or meloxicam [26] and of menthol with ibuprofen [7,25,27], testosterone [28], lidocaine [29], or ubiquinone [30] have been investigated as analgesic, antimicrobial and anti-inflammatory vehicles. Under the new DES perspective menthol-based eutectic mixtures with pyruvic, acetic, l-lactic and lauric acids were reported as hydrophobic, low viscosity, DES, and applied to the extraction of caffeine, tryptophan, isophthalic acid, and vanillin [31].…”
Section: Terpene-based Mixturesmentioning
confidence: 99%
“…Among the eutectic mixtures, the pae:men 4:6 system showed the highest solubility of paeonol (593.3 ± 26.6 lg/ml), which was even higher than the solubility of pure paeonol itself (537.9 ± 42.3 lg/ml). Similarly, Yong et al (2003) observed that the solubility of ibuprofen in water increased as the ratio of menthol to ibuprofen increased from 0:10 to 4:6, and then decreased as the ratio increasing from 4:6 to 10:0. These results suggested that the improved solubility of paeonol might be contributed by the formation of eutectic mixture of paeonol with menthol in the aqueous solution.…”
Section: Saturated Solubilitymentioning
confidence: 79%
“…Eutectic mixtures can be formed between excipients [borneol and menthol (Shen et al 2011)], between drug and excipient [Ibuprofen and menthol (Yong et al 2003)] or between drugs [lidocaine and prilocaine (Chun et al 2012)]. Each of them has proven to be effective in facilitating drug transport through the skin corneum.…”
Section: Introductionmentioning
confidence: 99%